2018
DOI: 10.4193/rhin17.165
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian tube symptoms are frequent in chronic rhinosinusitis and respond well to endoscopic sinus surgery

Abstract: Symptoms suggestive of ET dysfunction are frequent in CRS, and for most patients the symptoms will decrease post-ESS to a level comparable with a non-CRS population. Patients whose ET symptoms do not respond to ESS may represent a target population for emerging therapeutic options for ET dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 1 publication
3
30
2
Order By: Relevance
“…This has been confirmed recently in a combined multi-centre cohort of 131 patients with CRS based on responses to the SNOT-22 questions on ear fullness and ear pain (16) . Therefore, the classification of ETD as a "minor" symptom of rhinosinusitis should be re-evaluated.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This has been confirmed recently in a combined multi-centre cohort of 131 patients with CRS based on responses to the SNOT-22 questions on ear fullness and ear pain (16) . Therefore, the classification of ETD as a "minor" symptom of rhinosinusitis should be re-evaluated.…”
Section: Discussionmentioning
confidence: 63%
“…The mean (standard deviation) overall score was 2.8 (1.6) for the rhinology patients nus surgery (17) . Maniakas et al also confirmed that for most CRS patients, ETD symptoms will decrease post-endoscopic sinus surgery to a level comparable with a non-CRS population (16) .…”
Section: Resultsmentioning
confidence: 84%
“…The mechanism of development of ear effusion is unknown but may be related to other factors than probiotic administration, such as (i) deterioration of pre-existing Eustachian tube dysfunction and/or upper respiratory tract disease following withdrawal of therapy or (ii) performance of nasal irrigation. ET dysfunction is frequent in CRS patients particularly in those with severe disease (Stoikes and Dutton, 2005 ; Maniakas et al, 2018 ) and may deteriorate following withdrawal of CRS medication. This concept is supported by a recent clinical trial of 60 patients treated with Dupilumab or placebo for CRSwNP where otitis media developed in a patient in the untreated placebo group treated only saline irrigation (Bachert et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SNOT‐22 subdomain score analyses (rhinologic, extranasal rhinologic, ear/facial, psychological, and sleep symptom) have been presented in the literature . One recent publication, discussing the individual ear‐related symptom scores on the SNOT‐22 questionnaire, reported statistically significant differences pre‐ and post‐ESS . Nonetheless, the MCID in these single symptom score analyses has not been studied to date.…”
Section: Discussionmentioning
confidence: 99%